Studies on Irish families with autosomal dominant retinitis pigmentosa, congenital stationary night blindness and on mouse models of inherited retinopathies - Kenna, Paul F. (Trinity College (Dublin, Ireland). Department of Genetics, 2007)
This thesis describes over 17 years of research into the molecular genetics of inherited retinopathies including Retinitis Pigmentosa (RP), the most prevalent form of inherited blindness world-wide, and Congenital Stationary Night Blindness. The work described encompasses research involving families segregating autosomal dominant forms of the conditions, as well as investigations involving a variety of animal models. The largest human pedigree investigated, TCD M1, manifested a particularly early-onset form of autosomal dominant RP, with symptoms of night blindness and visual field loss evident before the age of 3 years. Family TCD M1 was the subject of extensive molecular genetic research to identify the causative gene, culminating in 1989 in the establishment of linkage to the Chromosome 3 polymorphic marker D3S47 (C17) with a LOD score of 14.7 at a recombination fraction of 0. This linkage, the first described in any form of autosomal dominant RP, pointed to the gene for the rod photoreceptor transduction protein, Rhodopsin, as a key candidate. In 1992 a Met207Arg mutation in this gene was identified in affected members of the TCD M1.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin